Semantic Knowledge Use in Discourse: Influence of Age. Issue 8 (17th November 2017) - Kintz, Stephen; Wright, Heather Harris
Abstract : Semantic memory is relatively stable across the lifespan (LaBarge, Edwards, & Knesevich, 1986). However, most research has been conducted at the single concept level (LaBarge et al., 1986, Spaniol et al., 2006). Few researchers have examined how semantic knowledge is used in discourse. The purpose of the study, then, was to determine the proportion of semantic knowledge and category domains used in discourse produced by younger and older participants. Cognitively healthy, younger ( n  = 30, aged 20–39) and older ( n  = 30, aged 60–89) participants told stories that were transcribed and coded for 10 domains of semantic knowledge and also living and nonliving things . Results indicated group differences for the proportion of semantic knowledge type, sound, and for the category type, living things. These findings extend previous research on semantic features into the realm of discourse and indicate the importance of studying semantic features and categories within discourse.